Creating tourism experiences combining food and culture: an analysis among Italian producers. Issue 2 (11th April 2018) - Garibaldi, Roberta; Pozzi, Andrea
Abstract : Purpose: This paper aims to understand how food and drink producers have combined food and culture into the tourism experience through an explorative analysis on a sample of Italian enterprises. Design/methodology/approach: The paper opted for a two-stage analysis. An explorative study has been carried out to identify producers with this offering and assess their main characteristics. A direct survey has been carried out to acquire detailed information about the profile of the enterprises as well as to assess motivations, results achieved and satisfaction concerning the experience offered. Findings: Food can be alternatively the main subject (e.g. food museums) or be combined with other cultural expression (e.g. music festivals inside wineries), and the choice appears to mainly depend on personal interest of entrepreneurs. The production of the food tourism experience not only increases the tourist attractiveness but also generates other benefits, such as improving brand visibility and relationship with local stakeholders. Research limitations/implications: Because of the sample chosen, the research results may lack generalizability. Furthermore, it may be important to deeply investigate some issues that remain partly unanswered. Practical implications: The paper sheds lights on characteristics of tourism experiences combining food and culture and hopefully aims at increasing awareness among producers about their current attractiveness. Originality/value: This paper tries to contribute to improve the knowledge on a topic of current interest such as tourism experiences combining food and culture.